4(m-12)=10m-6(m-8)

Simple and best practice solution for 4(m-12)=10m-6(m-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(m-12)=10m-6(m-8) equation:



4(m-12)=10m-6(m-8)
We move all terms to the left:
4(m-12)-(10m-6(m-8))=0
We multiply parentheses
4m-(10m-6(m-8))-48=0
We calculate terms in parentheses: -(10m-6(m-8)), so:
10m-6(m-8)
We multiply parentheses
10m-6m+48
We add all the numbers together, and all the variables
4m+48
Back to the equation:
-(4m+48)
We get rid of parentheses
4m-4m-48-48=0
We add all the numbers together, and all the variables
-96!=0
There is no solution for this equation

See similar equations:

| 10(-3+4)-3x=139 | | 10x+10+100=180 | | -8(2x-5)=2-10x | | 1.75+8x=8.15 | | -5x=-78 | | t=4-3+5 | | 6ww=5 | | 42a+18-19a=28 | | 6/7t-12=3/12t+15 | | 5(x+2)-3x=3x+5-2x+1 | | 1+w=-10 | | 3x+3+2x=8 | | 5x/3=x/15-9/5 | | a²-12a+20=0 | | -6(3x-8)=-18x+14 | | 2r+49=-8(-r=-5) | | x=1+2x=3x+1 | | 3x−63+9=18 | | -12=2m+4m | | -2(x-5)=6(3+1/3x) | | 180(x-2)=90x-1080 | | 189-x=94 | | x-1/5=3/7 | | 1=6(6x+6)-5 | | 8(1+2x)-8=96 | | 23x=23000 | | 8+3x+3=2x | | 3x-20=4x+10-x | | ((X^2)+(8x)+16)/((7x^2)+2)=0 | | x+1=2x=3x+1 | | 17x=595 | | 4.x+4=36 |

Equations solver categories